Performance of unpaved laterite road treated with chemical additives and waste tire - Sayyed Yaghoub Zolfeghari Far, 1979- , author; Khairul Anuar Kassim, supervisor; Mohd. Rosli Hainin, supervisor; Anuar Ahmad; Amin Eisazadeh Otaghsarae, supervisor; Fakulti Kejuruteraan Awam (2015)
Thesis (Ph.D (Kejuruteraan Awam - Geoteknik))- Universiti Teknologi Malaysia, 2015